Fluid processes in the early Earth and the growth of continents - Hartnady, Michael; Johnson, Tim; Schorn, S.; Hugh Smithies, R.; Kirkland, Christopher; Richardson, S.H. (ELSEVIER, 2022)
Water is an essential ingredient in transforming primitive mantle-derived (mafic) rocks into buoyant (felsic) continental crust, thereby driving the irreversible differentiation of Earth's lithosphere. The occurrence in Archaean cratons of sodic granites of the tonalite–trondhjemite–granodiorite (TTG) series, high-MgO variolitic basalts, high-Mg diorites (sanukitoids) and diamonds with harzburgitic inclusion assemblages, all require the presence of hydrous fluids in Earth's deep crust and upper (lithospheric) mantle since at least the Paleoarchaean (3.6–3.2 billion years ago). However, despite its importance, where and how water was stored in Archaean crust, and how some water was transported into the upper mantle, are poorly understood. Here, we investigate Archaean crustal fluid budgets through calculated phase equilibria for three protolith compositions — a low-MgO mafic (basaltic) composition, a high-MgO (picritic) composition and an ultrahigh-MgO ultramafic (komatiitic) composition — that are representative of mafic to ultramafic magmatic rocks in Archaean greenstone belts. We show that the mode and stability of hydrous minerals, in particular chlorite, is positively correlated with protolith MgO content, such that high-MgO basalts can store up to twice the amount of crystal-bound H2O than low-MgO basalts. Importantly, ultrahigh-MgO rocks such as komatiite can store four times as much H2O, most of which is retained until temperatures exceeding 700 °C. Warmer geotherms in the early Archaean favoured dehydration of hydrated high-MgO and ultramafic rocks in the deep crust, leading to hydration and/or fluid-fluxed melting of overlying basaltic rocks to produce ‘high-pressure’ TTG magmas. Burial of Archaean mafic–ultramafic crust along cooler geotherms resulted in dehydration of ultramafic material within the lithospheric mantle, providing the source of enriched Archaean basalt that was parental to large volumes of ancient TTG-dominated continental crust.